Multicore-shell carbon-coated lithium manganese phosphate and lithium vanadium phosphate composite material with high capacity and cycling performance for lithium-ion battery. (1st July 2015) - Zhang, Jia-feng; Wang, Xiao-wei; Zhang, Bao; Peng, Chun-li; Tong, Hui; Yang, Zhan-hong
Abstract: The energy crisis and energy security leads a great attention to Li-ion batteries (LIB) as the excellent power candidates. We successfully synthesized LiMnPO4 ·Li3 V2 (PO4 )3 /C composite cathode material with high capacity and excellent cycling performance from prickly MnV2 O6 ·2H2 O precursor, following chemical reduction and lithiation with double carbon sources. The LiMnPO4 ·Li3 V2 (PO4 )3 /C sample has a special multicore-shell structure, whose inner stuffing are LiMnPO4 and Li3 V2 (PO4 )3 in the range of 5-25nm. The initial discharge capacity of LiMnPO4 ·Li3 V2 (PO4 )3 /C composite delivers 221.4 mAh g −1, 202.3 mAh g −1 and 152.9 mAh g −1 at the rate of 0.1C, 1C and 5C in the range of 1.5-4.5 V, and retains 99.5%, 99.1% and 94.3% of its initial discharge capacity after 50 cycles, respectively.